Vidros tardios do Castro de Guifões: formas, técnicas e trajectos - Arezes, Andreia (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2019)
The aim of this text is to present a set of glasses collected in Castro de Guifões (Matosinhos), in the first campaign of excavations carried out under the GUIFARQ Project. The recovery of these elements provided a basis for material study, from which classifications and frameworks were proposed; also, lines of reflection were drawn around the importance of glass and its circulation in Late Antiquity. Relating mainly to tablewarealmost all these glasses result from local or regional production activity. Importation, in turn, is represented at least in a single, but remarkable, occurrence: a fragment of a bowl bearing engraved figurative decoration, currently unparalleled in the Iberia Peninsula Northwest.